Investigating the Impact of Firm-specific and Macroeconomic Determinants of Operating Efficiency of Commercial Banks: Panel Evidence from Bangladesh - Lalon, Raad Mozib; Mili, Afrin Rahman (International Journal of Economics and Financial Issues, 2023)
This paper aims to find out the significant firm-specific and macroeconomic determinants of operating efficiency through covering 360 observations having 30 commercial banks’ data from 2009 to 2020. Model specification test along with several diagnostic tests has been done and our investigation reveals that Net interest margin or net investment income ratio, loan loss provision to total loan, debt to total assets and total loan to earning assets are significantly related with operating efficiency ratio (OER) bringing the changes in operating efficiency. In the second model, return on equity, net interest margin or net investment income ratio, equity capital to total assets, loan loss provision to total loan, bank size, total loan to earning assets and total loan to total deposit significantly affect the operating efficiency of commercial banks being measured with cost efficiency ratio (CER). In the subsequent model, net interest margin or net investment income ratio, total loan to earning assets, debt to total assets ratio, and total loan to total deposit have been evidenced to affect the operating efficiency significantly being measured with operating expense to earning assets ratio (OEEAR).